Development and validation of a mechanistic model for the release of embelin from a polycaprolactone matrix. (November 2020) - Seoane, Irene T.; Cortez Tornello, Pablo R.; Silva, Leonel; Tomba, J. Pablo; Abraham, Gustavo A.; Cisilino, Adrián
Abstract: Embelin is a natural agent with antimicrobial, antifungal and analgesic activities. This work presents a mechanistic model for the release of embelin from a polycaprolactone matrix. Based on the results of embelin release experiments and Raman microscopy measurements, the model assumes a dual dispersion of the embelin: agglomerated and dispersed. Embelin release mechanism combines the effects of the liquid migration into the matrix, the drug diffusion, and the drug dissolution within the wetted matrix. The model is formulated in terms of four partial differential equations that account for the mass balances of dispersed, agglomerated, and dissolved embelin, and aqueous solution. Model predictions show that the release mechanism involves three stages: a burst stage, in which dispersed embelin is rapidly released; a transition stage, in which dispersed and agglomerated embelin are simultaneously released; and, once the dispersed embelin depletion, a stable release stage until the agglomerated embelin exhausts. Highlights: Embelin is released after being dissolved by the solution entering the sample. The solution diffusion coefficient is the critical parameter for the model tuning. Disperse embelin is liberated during the rapid initial release stage. Superficial agglomerated embelin is liberated during the long-lasting stable stage. Raman microscopy validates the model set-up and results.